Perbandingan Percepatan Penyembuhan Phlebitis dengan Menggunakan Terapi Topical Heparin Sodium Gel dan Kompres Hangat - Widyah Ayu Sri Gunawati; Feriana Ira Handian (Jurnal Ilmiah Kesehatan Rustida, 2021)
The purpose of this research is to find out the phlebitis healing acceleration difference using heparin sodium gel topical therapy compared to warm compresses to pediatric patient in pediatric surgery ward in RSUD dr. Saiful Anwar Malang. The method used in this research is quantitative with observative design. The sampling is using total sampling technique is using purposive technique with 16 toddler participants. Descriptively the healing process using heparin sodium gel needs around 0.75 hour faster. This can be affected by some factors such as age, nutritions status, disease status, the medicines gives, radiation, life style or the stress level. With Mann Whitney test analysis, with 5% error level, the phlebitis healing time using heparin sodium gel therapy (9,625), is not significantly different in statistic the value of p (0.721) or p> 0,05 if compared with the average phlebitis healing time by using warm compresses (10,375). So statistically there is no significant difference between the phlebitis healing time acceleration with the application of heparin sodium gel therapy compared to warm compresses. Suggestion for the next researcher, the research sample is taken by equalize the factors that caused phlebitis, such as age, nutritions status, disease status, the medicines gives, radiation, life style or the stress level, veins condition, type of disease, sex, chemical factor, mechanical factor, bacterial factor, and also add the sample amount to give a better research result.